2022
DOI: 10.1021/acssuschemeng.2c03138
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Bioactive Salts Fully Composed of Natural Products for Enhanced Pharmaceutical Applicability

Abstract: Phenolic acids are attractive plant-derived bioactive substances owing to their wide range of pharmaceutical properties for the prevention of various human diseases as well as their applications in adjuvant therapy. However, phenolic acids exhibit poor water solubility, which limits their bioavailability and applications. In this study, phenolic acids were combined with matrine to form salts. Matrine is an alkaloid from a traditional Chinese herb that also has abundant pharmaceutical features and was employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Indeed, such removal could imply additional costly and energy-consuming downstream processing steps such as membrane filtrations [20]. In an ideal situation, salts should remain in the final product not only to simplify the process but also to potentially stabilise the extracted NP or even to enhance its properties (compared to those of the free NP solubilised in water) [21].…”
Section: Ph Range and Saltsmentioning
confidence: 99%
“…Indeed, such removal could imply additional costly and energy-consuming downstream processing steps such as membrane filtrations [20]. In an ideal situation, salts should remain in the final product not only to simplify the process but also to potentially stabilise the extracted NP or even to enhance its properties (compared to those of the free NP solubilised in water) [21].…”
Section: Ph Range and Saltsmentioning
confidence: 99%
“…The chemical characteristics of natural waters are the reflection of the soils and rocks which have been in contact with water. The quality and quantity of the chemical elements in surface waters is affected by geo‐chemical structure of surrounding area, land use, seasonal variations of weather conditions, vegetation and the atmospheric deposit [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of salt is similar to the formation of cocrystals, which are complexes formed by the transfer of protons from acidic components to alkaline components and the combination of the active pharmaceutical ingredient (API) and cocrystal formers (CCFs) or salt formers (SFs) through hydrogen bonding [ 23 , 24 , 25 ]. Previous studies have demonstrated that MAT can form salts with acids by proton transfer reaction while maintaining its biological activity [ 26 , 27 ]. Mi et al [ 26 ] formed MAT salts with syringic acid (SYR), vanillic acid (VAN), protocatechuic acid (PRO), caffeic acid (CAF), and gallic acid (GAL).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that MAT can form salts with acids by proton transfer reaction while maintaining its biological activity [ 26 , 27 ]. Mi et al [ 26 ] formed MAT salts with syringic acid (SYR), vanillic acid (VAN), protocatechuic acid (PRO), caffeic acid (CAF), and gallic acid (GAL). The obtained salts showed improved anticancer, antioxidant, and anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%